Combating Post-Covid-19 Social Inequality among Learners in Primary and Post-Primary Schools in Uganda - Kyohairwe, Stella B.; Muriisa Kabeba, Roberts; Karyeija, Gerald K. (Africa Journal of Public Sector Development and Governance, 2020)
Following the World Health Organization (WHO) announcement that COVID-19 is a global pandemic because of the many lives it had claimed worldwide in March 2020, education institutions are some of the hard-hit areas of the economy. With many countries taking drastic decisions to close education institutions, the biggest dilemma faced by governments and policymakers between closing schools within barely weeks of opening for the first quarter of the 2020 calendar year, was a trade-off between accomplishing the required curriculum of the education programs and saving lives from the coronavirus. Education institutions, including schools, colleges and universities, proved to be among the high population concentration centres4. The challenge facing schools is that apart from having many people interacting on a daily basis (both learners and instructors), there is a dynamic, interactive exchange between external persons and those residing within the physical boundaries of schools. This increases the chances for the spread of the deadly coronavirus infection. The complexity of having the non-boarding educational institutions where learners and teachers interact regularly with local communities, poses a threat with regard to community transmission of coronavirus, which is likely to create a health crisis that Uganda’s weak economy is currently ill-prepared to handle.
Keywords: Post-Covid-19; Social Inequality; Learners; Post-Primary Schools